Optimalisasi penerapan Dietary Approaches to Stop Hypertension (DASH) pada Penderita Hipertensi - Nurul Laili; Enur Nurhayati Muchsin; Jundah Erlina (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Preventive management of hypertension sufferers is a priority in the health care system to prevent morbidity and mortality. One of the ways to treat hypertension is to do a diet program by implementing DASH (Dietary Approaches to Stop Hypertension) which can control blood pressure. DASH is a method to control hypertension by adjusting diet including sodium intake. energy intake, amount and type of protein, as well as fat and carbohydrate components. Objective: The purpose of community service activities is to provide education about the application of DASH and provide health services to people with hypertension. Method: The method of community service activities is education and data collection using interviews and questionnaires. The activity was carried out for 3 days from March 31 to April 2, 2022 in the working area of ​​the Puhjarak Health Center, Kediri Regency. Participants in the counseling were patients with hypertension. The counseling participants were 20 people.   Result: The result of knowledge before being given education shows sufficient understanding about the implementation of DASH. Good supporting facilities and infrastructure have an influence on the implementation of DASH on a person. Lack of knowledge caused some participants to not get sufficient access to reach the correct information. Hypertension sufferers who are less active in seeking information and the inefficient implementation of health promotion is a significant cause of the lack of understanding and adherence of hypertension sufferers to the application of DASH. Conclusion: Efforts to prevent and treat hypertension are carried out through health education for the community. The government through health services seeks to improve health promotion through communication, information and education. Providing education to the public can increase knowledge, awareness and desire of the community to prevent hypertension.